1936
DOI: 10.1017/s0021859600022723
|View full text |Cite
|
Sign up to set email alerts
|

The value of artificially dried grass, silage made with added molasses and A.I.V. fodder in the diet of the dairy cow and their effect on the quality of the milk, with special reference to the value of the non-protein nitrogen

Abstract: An experiment has been carried out with dairy cows to measure the value of artificially dried grass, silage made with added molasses and A.I.V. fodder (silage made with mineral acid in quantity sufficient to bring the pH of the mass to between 3·0 and 4·0) in the diet, on the yield and quality of the milk. A preliminary period of 3 weeks when all cows were on the control diet was followed by an experimental period of 17 weeks. There were four treatments: a control ration consisting of hay, roots and concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1936
1936
1967
1967

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Modern work has shown that the breakdown products of the "true" protein are of high nutritive value if the process has not proceeded too far, and this has been demonstrated by the authors (16). It is, therefore, more accurate to make allowance for this fact, and the corrected digestible "true" protein value is designed to meet the case.…”
Section: Composition and Digestibility Of Fresh Grass And Molassed Simentioning
confidence: 98%
See 2 more Smart Citations
“…Modern work has shown that the breakdown products of the "true" protein are of high nutritive value if the process has not proceeded too far, and this has been demonstrated by the authors (16). It is, therefore, more accurate to make allowance for this fact, and the corrected digestible "true" protein value is designed to meet the case.…”
Section: Composition and Digestibility Of Fresh Grass And Molassed Simentioning
confidence: 98%
“…process over ordinary or molassed silage is not so great as it is usually thought to be. The breakdown of "true" protein is reduced to a marked extent by the addition of acid, but so long as the decomposition has not proceeded too far, this, as has been pointed out (16), is no great disadvantage.…”
Section: Losses Of Dry Matter and Nutrients In Silagementioning
confidence: 99%
See 1 more Smart Citation
“…value is over 4-5. Below this level, the only change which occurs down to pH 2-5 is a reduction in the percentage of volatile bases from 9 to 4 per cent, a small change, negligible for most purposes. The somewhat greater formation of amino acids in molassed silage is of little import, since recent work at this Station (22) has shown that for milk production this fraction has a value which does not differ markedly from that of true protein.…”
Section: Protein Breakdown Of Silagementioning
confidence: 99%
“…These coefficients cannot, however, easily be separated from the treatment means, and for properly randomised experiments, in which the usual analysis is always a valid one, this modification would hardly ever be worth while. In a discussion (5) on this point in the design and analysis of dairy cow nutrition experiments, this conclusion was made provisionally, but has been substantiated by the actual results of an experiment conducted and analysed on the lines proposed (6).…”
mentioning
confidence: 96%